Original Alvarado scoring system in the diagnosis of acute appendicitis: A cohort study. - Çalışkan, Yahya Kemal (Journal of Surgery and Medicine, 2017)
Aims: Although acute appendicitis is the most common cause of acuteabdomen, there is still no definitive diagnostic method. Various scores weredefined in the literature. In this study, we investigated the effectiveness ofthe Alvarado score, a clinical scoring system aimed at supporting thediagnosis. Methods: Patients who were to be operated with acute abdomen and acuteappendicitis pre-diagnosis in our hospital emergency surgery service werecalculated before the Alvarado scores. This score has 8 parameters in thesystem. 1-The right lower quadrant of pain, 2-anorexia, 3-nausea-vomiting,4-right lower quadrant sensitivity, 5-rebound sensitivity, 6-fever,7-leukocytosis, 8-left shift (granulocytosis). Numbers 4 and 7 are calculatedwith a total of 10 points, 2 points, 1 point. Results: Total 200 patients, (128 males, 82 female, male/female: 1.6)mean age was 34.3 ± 15.6, and the age range was 15-78. In ROC analysis,Alvarado scores greater than 6 has demonstrated acute appendicitis diagnosiswith 76% sensitivity and 91% specificity. Alvarado score of 9-10 showed 100%sensitivity to detect acute appendicitis. Conclusions: Clinical scoring systems are frequently used in thediagnosis of acute appendicitis. In publications covering the Alvarado scoresof 9-10, the high probability of appendicitis, needs surgical intervention, andadvanced examination methods were proposed in scores of 7-8. Our study resultedin consistent with the literature.